Modeling and Configuration Optimization of Spatial Angle Diversity Reception for Underwater Multi-Faceted Optical Base Station - Junjie Shi; Jun Ao; Chunbo Ma; Xu Tian; Hanjun Guo (Photonics)
Compared with point-to-point underwater wireless optical communication (UWOC) systems with a single direction, the underwater multi-faceted optical base station (OBS) offers independent fields of view and directions for each receiving detector, supporting multiple user access and mobile communication. This study aims at the issue of link interruptions and a limited communication area caused by restricted OBS receiver fields of view when underwater devices move. A field-of-view model and spatial angle diversity reception framework for the multi-faceted OBS in underwater channels have been developed, visualizing the effective reception field of the OBS. This model helps analyze the impact of multi-faceted OBS detector layouts on link performance in underwater environments. Furthermore, under constraints on the number of detectors, configuration adjustments are made to the field-of-view angles and deflection angles of detectors. Simulation results show that, under the same typical underwater environmental conditions, the optimized configuration reduces the blind area compared to the typical configuration, enhancing the effective spatial field of view of the OBS receiver by over 10%. The OBS’s effective communication coverage for mobile devices on different planes is also improved. This research provides a theoretical model and parameter configuration guidelines for the design of the underwater multi-faceted OBS.